PERBAIKAN VIABILITAS DAN KUALITAS FISIK BENIH TOMAT MELALUI PENGATURAN LAMA FERMENTASI DAN PENGGUNAAN NaOCl PADA SAAT PENCUCIAN BENIH - Gungun Wiguna (Universitas Wahid Hasyim, 2013)
This study aims to determine the effectiveness of arrangements between fermentation time and using NaOCl when washing the tomato seeds to improving the physical quality of the seed without decreasing seed viability. The experiment was conducted in May 2011 at the Laboratory of Seed Technology, Vegetable Crops Research Institute, Lembang. Research using tomato strain 6046 CLN physiologically ripe. Each treatment consisted of 25 grains of seed and repeated 4 times. The experiments were performed using analysis of completely randomized design (RAL). The results showed that the longer the time needed for fermentation, the pulp will be more easily separated from the seed. Washing using bayclin solution can improve the physical properties of tomato seed so that the color becomes brighter without causing a decrease in viability and vigor. Keywords: Fermentation, tomato, viability, vigor.